2018
DOI: 10.1242/bio.034678
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PKCε in FSH-induced connexin43 phosphorylation and oocyte maturation in mouse

Abstract: Gap junctions (GJs) are indispensable for communication between cumulus cells (CCs) and oocytes in coordinating the gonadotropin-induced meiotic maturation of oocytes. Of all proteins that constitute GJs, phosphorylated connexin43 (pCx43) is vital for mediating the actions of gonadotropins. In this study, the mechanism of Cx43 phosphorylation in response to follicle stimulating hormone (FSH) stimulation was examined using an in vitro model of mouse cumulus-oocyte complexes (COCs). The results confirmed that Cx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…In contrast, intra-CC cAMP levels exhibited two peaks at 10 min and 1 h, respectively. These observations are consistent with previous studies reporting transient increases in intra-oocyte cAMP when mouse COCs were treated with FSH or LH alone for 30 min or 1 h ( 16 , 19 ). Another study showed that FSH, alone or in combination with LH, could significantly elevate intra-CC cAMP content in mouse or sheep COCs for 1 h ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, intra-CC cAMP levels exhibited two peaks at 10 min and 1 h, respectively. These observations are consistent with previous studies reporting transient increases in intra-oocyte cAMP when mouse COCs were treated with FSH or LH alone for 30 min or 1 h ( 16 , 19 ). Another study showed that FSH, alone or in combination with LH, could significantly elevate intra-CC cAMP content in mouse or sheep COCs for 1 h ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 93%
“…Blocking gap junctions with specific blockers in mice ( 12 ) and rats ( 13 ), or artificially separating the somatic compartment from the oocytes of intact hamster follicles ( 14 ), can lead to oocyte germinal vesicle breakdown (GVBD). Therefore, it is speculated that gonadotropin-induced gap junction closure prevents inhibitors in CCs from reaching oocytes, eventually leading to meiotic resumption ( 15 , 16 ). However, this hypothesis is not fully considered.…”
Section: Introductionmentioning
confidence: 99%
“…For these non-physiological features, we should furtherly considercertain unfavourability ofGnRHawhen using it to trigger the oocyte maturation process.It is widely acknowledged that, under COS conditions, poor oocyte quality and embryo development partly lie in a stubborn asynchrony between nuclear and cytoplasmic maturationprocess of oocytes [31,32]. Despite the explicit underlying mechanism underlying this asynchrony remainselusive, a premature resumption of oocyte meiosis induced byexogenous pharmacological drugs, including GnRHaor HCGmaypresumablyplay an important role.Basic researches have indicated that the transportation of signal molecules, nutrients, and energy substrates through the gap junction, from cumulus cell to oocytes, be requisite for not onlyoocyte nuclear maturation, but also its cytoplasmic maturation [33,34].In respond to the LH surge and its downstream ovulatory signals, such as EGF-like peptides (including AREG, EREG and BTC), EGFR-ERK1/2 as well as NPPC-NPR1 signal pathways [35][36][37], a diminished phosphorylation of Cx43 and a consequential closure of gap junction between oocytes and cumulus cells will emerge in concurrence with the meiosis resumption and progress, i.e., nuclear maturation [38][39][40]. In terms of the pharmacokinetics, the peak time of hCGafter administration is about 12h [41], while the LH peak induced by GnRHaonly 4h [30], which is evenprecocious in relation to thenatural cycles.This relative premature LH surge may induce anuntimely interruption of the junction between oocytes and cumulus cells, which in turn, eliminate the accumulation of oocyte quality factors such as signal molecules, nutrients, and energy substrates, and eventuallyaggravate the asynchrony between nuclear and cytoplasmic maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, Cx43 is mainly expressed in gap junctions between GCs and is regulated by extracellular signal regulated kinase-1 and -2 (ERK1/ERK2) signals in response to LH surge in vivo ( Su et al, 2002 ; Sela-Abramovich et al, 2005 ; Dekel, 2009 ). However, PKCε-mediated mitogen-activated protein kinase (MAPK)-dependent signals might contribute to Cx43 phosphorylation in CGCs during FSH-induced oocyte meiotic resumption in vitro ( Cai et al, 2018 ). Ovaries lacking Cx43 do not proceed beyond the primary follicle stage.…”
Section: Oocyte Nuclear Maturationmentioning
confidence: 99%